Positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

By using a composite metal oxide positive electrode active material containing Ca and Sr surface modification layers in the nonaqueous electrolyte secondary battery, the problem of low charge and discharge efficiency in the prior art is solved, and higher charge and discharge efficiency and diffusion are achieved.

CN119678265APending Publication Date: 2025-03-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380058433.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-06-28
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

There is room for improvement in the charging and discharging efficiency of existing nonaqueous electrolyte secondary batteries, especially in high output applications.

Method used

A composite metal oxide containing at least one element selected from the group consisting of Li, B, Na, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi is used as the positive electrode active material. The composite metal oxide contains secondary particles formed by the aggregation of primary particles, and the proportion of primary particles containing an aspect ratio of 2 or more is more than 35%. At the same time, a surface modification layer containing Ca and Sr is present on the surface of the primary particles.

Benefits of technology

Through this technical means, the charging and discharging efficiency of the nonaqueous electrolyte secondary battery is significantly improved, and the diffusion and intercalation and disengagement ability between the positive electrode active material and the nonaqueous electrolyte are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119678265A_ABST
    Figure CN119678265A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode active material which contributes to improving the charge / discharge efficiency of a non-aqueous electrolyte secondary battery. The positive electrode active material contained in the non-aqueous electrolyte secondary battery contains a composite metal oxide containing at least one element selected from the group consisting of Li, B, Na, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi, the composite metal oxide contains secondary particles formed by aggregating primary particles, and among the secondary particles, the positive electrode active material contains at least one element selected from the group consisting of Li, B, Na, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi. The proportion of the primary particles having an aspect ratio of 2 or more is 35% or more with respect to the total number of the primary particles, and a surface modification layer containing Ca and / or Sr is present on the surfaces of the primary particles including the surfaces of the secondary particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art

[0002] In recent years, the use of non-aqueous electrolyte secondary batteries has expanded to power supplies for electric vehicles and power storage devices for utilizing natural energy. The properties required of the positive electrode active material used in non-aqueous electrolyte secondary batteries also vary depending on the use. For example, Patent Document 1 discloses a positive electrode active material in which the proportion of primary particles with a large aspect ratio in the surface portion of the secondary particles is greater than the proportion of primary particles with a large aspect ratio in the central portion of the secondary particles.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 6550598 Summary of the invention

[0006] In order to increase the output, nonaqueous electrolyte secondary batteries are sometimes required to improve the charge and discharge efficiency. The technology described in Patent Document 1 does not study the improvement of the charge and discharge efficiency, and there is still room for improvement.

[0007] An object of the present disclosure is to provide a positive electrode active material that contributes to improving the charge and discharge efficiency of a non-aqueous electrolyte secondary battery.

[0008] A positive electrode active material for a non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it comprises a composite metal oxide containing at least one element selected from the group consisting of Li, B, Na, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi, the composite metal oxide comprises secondary particles formed by aggregation of primary particles, in which the proportion of primary particles having an aspect ratio of 2 or more relative to the total number of primary particles is 35% or more, and a surface modification layer containing at least one of Ca and Sr is present on the surface of the primary particles including the surface of the secondary particles.

[0009] A nonaqueous electrolyte secondary battery as one embodiment of the present disclosure is characterized by comprising a positive electrode including the above-mentioned positive electrode active material, a negative electrode, and a nonaqueous electrolyte.

[0010] According to the positive electrode active material for a nonaqueous electrolyte secondary battery as one embodiment of the present disclosure, a nonaqueous electrolyte secondary battery having improved charge and discharge efficiency can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0012] Figure 2 is a diagram schematically showing the structure of a primary particle with a high aspect ratio. DETAILED DESCRIPTION

[0013] The inventors of the present invention conducted intensive research and found that the surface of the positive electrode active material is protected by a surface modification layer containing Ca or Sr, and the positive electrode active material composed of secondary particles contains primary particles with an aspect ratio of 2 or more in a specified proportion, thereby specifically improving the charge and discharge efficiency.

[0014] Before the positive electrode active material is assembled into the battery, it sometimes reacts with water during manufacturing and storage to form a metamorphic layer on the surface. In addition, after the positive electrode active material is assembled into the battery, it sometimes reacts with the non-aqueous electrolyte to form a metamorphic layer on the surface. The metamorphic layer inhibits the embedding and detachment of the alkaline component between the positive electrode active material and the non-aqueous electrolyte, thereby reducing the charge and discharge efficiency. It is speculated that the formation of the metamorphic layer is suppressed by the surface modification layer containing Ca or Sr. In addition, it is speculated that the positive electrode active material composed of secondary particles improves the diffusibility of the non-aqueous electrolyte into the secondary particles by containing primary particles with an aspect ratio of more than 2 in a specified proportion, and the secondary particles as a whole achieve the embedding and detachment of the alkaline component.

[0015] Hereinafter, an example of an embodiment of a non-aqueous electrolyte secondary battery according to the present disclosure is described in detail. Hereinafter, although a cylindrical battery in which a wound electrode body is contained in a cylindrical outer casing is exemplified, the electrode body is not limited to a wound type, and may also be a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated one by one through a separator. In addition, the outer casing is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc., or may be a battery casing composed of a laminated sheet including a metal layer and a resin layer.

[0016] Figure 1 FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. Figure 1 As shown, the secondary battery 10 includes a wound electrode body 14, an electrolyte, and an outer body 16 that contains the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer body 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer body 16 is blocked by a sealing body 17. In the following, for the sake of convenience of explanation, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer body 16 is set as the lower side.

[0017] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all rectangular strips, which are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape in the length direction. The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The two separators 13 are formed to be at least one circle larger than the positive electrode 11, for example, arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 becomes the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 becomes the axial direction. That is, the end faces of the positive electrode 11 and the negative electrode 12 in the width direction form the end faces of the electrode body 14 in the axial direction.

[0018] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer body 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the cover 27 as the top plate of the sealing body 17 electrically connected to the internal terminal plate 23 becomes the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer body 16 by welding or the like, and the outer body 16 becomes the negative terminal.

[0019] A sealing gasket 28 is provided between the outer body 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer body 16 so that a part of the side portion bulges inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumference of the outer body 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer body 16 through the groove portion 22 and the open end portion of the outer body 16 that is closely fitted to the sealing body 17.

[0020] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating component 25, an upper valve body 26 and a lid 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating component 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat, the lower valve body 24 deforms and breaks to push the upper valve body 26 to the lid 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the lid 27.

[0021] Hereinafter, the positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the secondary battery 10 , particularly the positive electrode 11 , will be described in detail.

[0022] [positive electrode]

[0023] The positive electrode 11 includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer is preferably formed on both sides of the positive electrode current collector. The positive electrode current collector may be made of a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.

[0024] The positive electrode mixture layer includes, for example, a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm on one side of the positive electrode collector. The positive electrode 11 can be produced, for example, by coating a positive electrode mixture slurry including a positive electrode active material, a conductive agent, etc. on the surface of the positive electrode collector and then rolling the coating after drying to form the positive electrode mixture layer on both sides of the positive electrode collector.

[0025] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0026] As the binder contained in the positive electrode mixture layer, for example, fluorine resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, polyacrylonitrile (PAN), etc. can be listed. These can be used alone or in combination of two or more.

[0027] The positive electrode active material contained in the positive electrode mixture layer includes a composite metal oxide. The composite metal oxide contains at least one element selected from the group consisting of Li, Na, B, Ni, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi and contains at least one of Ca and Sr.

[0028] The composite metal oxide contains, for example, an alkali metal, and the alkali metal is preferably Li.

[0029] Relative to the total molar number of metal elements other than alkali metals, the content of Ni in the composite metal oxide is, for example, 50 mol%≤Ni content≤95 mol%. From the perspective of both high capacity and structural stabilization, the Ni content is preferably within this range. The lower limit of the Ni content is preferably 70 mol%, more preferably 80 mol%.

[0030] The content of Co in the composite metal oxide relative to the total molar number of metal elements other than alkali metals is, for example, 0 mol% ≤ Co content ≤ 15 mol%. From the perspective of cost reduction, the Co content is preferably within this range. The upper limit of the Co content is preferably 12 mol%.

[0031] Relative to the total molar number of metal elements other than alkali metals, the content of Mn in the composite metal oxide is, for example, 0 mol%<Mn content≤40 mol%. From the perspective of both high capacity and safety, the Mn content is preferably within this range. The lower limit of the Mn content is preferably 1 mol%, more preferably 3 mol%. The upper limit of the Mn content is preferably 30 mol%, more preferably 10 mol%.

[0032] In the composite metal oxide, the Co content and the Mn content preferably satisfy 0≤Co content / Mn content≤2.

[0033] In addition to alkali metals, Ni, Co, Mn, Ca and Sr, the composite metal oxide may also contain Me (Me is at least one element selected from the group consisting of B, Mg, Al, Si, P, Ti, Fe, Zr, Nb, Mo, Sn, W and Bi). Relative to the total molar number of metal elements other than alkali metals, the content of Me in the composite metal oxide is, for example, 0 mol%≤Me content≤20 mol%. From the perspective of both high capacity and structural stabilization, the Me content is preferably within this range. The upper limit of the Me content is preferably 10 mol%.

[0034] The sum of the contents of Ca and Sr in the composite metal oxide is preferably 0 mol% <Ca content + Sr content < 2 mols relative to the total molar number of metal elements other than alkali metals. The lower limit of the sum of the Ca content and the Sr content is preferably 0.01 mol%, more preferably 0.1 mol%. The upper limit of the sum of the Ca content and the Sr content is, for example, 1.9 mol%.

[0035] The composite metal oxide preferably satisfies the relationship of Ca content>Sr content. This can significantly improve the charge and discharge efficiency of the secondary battery.

[0036] The composite metal oxide preferably contains both Ca and Sr. This can significantly improve the charge and discharge efficiency of the secondary battery.

[0037] For example, a composite metal oxide is composed of the general formula Li a Ni x Co y Mn z Me w Ca s Sr t O 2-bThe composite oxide represented by the formula, wherein 0.8≤a≤1.2, 0.5≤x≤0.95, 0≤y≤0.15, 0<z≤0.4, 0≤w≤0.20, 0<s+t<0.02, 0≤b≤0.05, x+y+z+w+s+t=1, and Me is at least one element selected from the group consisting of B, Mg, Al, Si, P, Ti, Fe, Zr, Nb, Mo, Sn, W and Bi). The proportion of the metal elements contained in the composite metal oxide can be measured, for example, by an inductively coupled plasma atomic emission spectrometer (ICP-AES).

[0038] The composite metal oxide includes secondary particles formed by the aggregation of primary particles. The particle size of the primary particles is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is measured by the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (hereinafter referred to as SEM, such as JSM-7900F manufactured by JEOL Ltd.). The average particle size of the secondary particles is, for example, 2 μm to 30 μm. Here, the average particle size refers to the median particle size (D50) based on volume. D50 refers to the particle size when the cumulative frequency in the volume-based particle size distribution reaches 50% from the side with a smaller particle size, also known as the median diameter. The particle size distribution of the secondary particles can be measured using a laser diffraction particle size distribution measuring device (such as MT3000II manufactured by Microtrac Bell) and water as the dispersion medium.

[0039] There is a surface modification layer containing at least any one of Ca and Sr on the surface of the primary particles including the surface of the secondary particles. Thus, the side reaction between the primary particles and the non-aqueous electrolyte can be significantly suppressed. The surface modification layer can be evenly dispersed on the entire surface of the primary particles including the surface of the secondary particles of the composite metal oxide, or it can be present on a part. The presence of Ca and Sr in the surface modification layer can be confirmed, for example, by energy dispersive X-ray spectroscopy (TEM-EDX). In the surface modification layer, Ca and Sr exist, for example, in the form of oxides.

[0040] At least one of Ca and Sr may be present in the surface modification layer and within 30 nm of the surface of the primary particle. This makes the effect of suppressing the side reaction more significant.

[0041] In the secondary particles, the proportion of primary particles 30 having an aspect ratio of 2 or more (hereinafter sometimes referred to as high aspect ratio primary particles 30) is 35% or more relative to the total number of primary particles. As a result, the diffusion of the non-aqueous electrolyte into the secondary particles is improved, and the secondary particles as a whole achieve the embedding and detachment of the alkali component. From the perspective of high capacity, the proportion of high aspect ratio primary particles 30 relative to the total number of primary particles is preferably 75% or less.

[0042] The ratio of the high aspect ratio primary particles 30 is calculated as follows.

[0043] (1) Exposing the cross section of the secondary particle As a method for exposing the cross section, for example, there is a method in which the secondary particle is embedded in a resin and processed using a cross section polisher (eg, IB19520CCP manufactured by JEOL Ltd.) to expose the cross section of the secondary particle.

[0044] (2) A reflected electron image of the cross section of the exposed secondary particles is taken using a SEM.

[0045] (3) The cross-sectional image obtained above is input into a computer, and the aspect ratio of each primary particle is calculated using image analysis software (e.g., ImageJ manufactured by the National Institutes of Health, USA). The aspect ratio of a primary particle is obtained by dividing the length of the long side of the primary particle by the length of the short side in the direction perpendicular to the longest diameter.

[0046] (4) Based on the above measurement results, the content rate of the high aspect ratio primary particles 30 is calculated according to the following formula.

[0047] (Content ratio of high aspect ratio primary particles 30) = (Number of high aspect ratio primary particles 30) / (Total number of primary particles) × 100

[0048] (5) The above measurement is performed on five secondary particles contained in the same composite metal oxide, and the average value thereof is defined as the ratio of the high aspect ratio primary particles 30 .

[0049] The composite metal oxide may have a layered structure in which alkali metal layers and Me layers are alternately stacked. Examples of the layered structure of the composite metal oxide include a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, a layered structure belonging to the space group P6 3 From the viewpoint of increasing the capacity and the stability of the crystal structure, the composite metal oxide preferably has a layered structure belonging to the space group R-3m.

[0050] In the secondary particles, the ratio of primary particles in which the edge faces of the alkali metal layer and the edge faces of the Me layer are oriented along the long diameter direction is preferably 70% or more relative to the total number of primary particles. As a result, the charge and discharge efficiency is further significantly improved. In the secondary particles, the ratio of primary particles in which the edge faces of the alkali metal layer and the edge faces of the Me layer are oriented along the long diameter direction relative to the total number of primary particles can be 100% or less, or 90% or less.

[0051] The ratio of primary particles in which the edge faces of the alkali metal layer and the edge faces of the Me layer are oriented in the major axis direction can be obtained from the results of orientation analysis of the edge faces under the following conditions using electron backscatter diffraction (EBSD) of a cross section of a positive electrode active material (eg, manufactured by Velocity EDAX).

[0052] Accelerating voltage: 10 kV

[0053] WD: 15mm

[0054] Sample tilt: 70°

[0055] Direction Analysis: Inverted Pole Figure Map

[0056] Step size: 0.05 μm

[0057] Figure 2 Schematic diagram showing the structure of the high aspect ratio primary particle 30. The edge surface 32 of the alkali metal layer and the edge surface 34 of the Me layer are oriented along the long diameter direction of the high aspect ratio primary particle 30. Figure 2 As shown, the edge faces 32 of the alkali metal layer and the edge faces 34 of the Me layer are alternately stacked in the short diameter direction of the high aspect ratio primary particle 30. In other words, the edge faces 32 of the alkali metal layer and the edge faces 34 of the Me layer are oriented perpendicular to the short diameter direction of the high aspect ratio primary particle 30. It should be noted that the orientation of the edge faces along the long diameter direction means that the edge faces are arranged roughly parallel to the long diameter direction. Specifically, the orientation of the edge faces along the long diameter direction means that the inclination of the edge faces relative to the long diameter direction is within the range of one-half of the angle between the edge faces and the base surface. The edge face refers to the end of the layered structure (the surface exposed in the stacked state), and the base surface refers to the face of the layered structure (the surface exposed on one side of the layer).

[0058] The alkali metal is Li, and the alkali metal layer can be a Li layer. In other words, the composite metal oxide can have a layered structure in which Li layers and Me layers are alternately stacked. The proportion of metal elements other than Li present in the Li layer of the layered structure is 8 mol% or less relative to the total molar number of metal elements other than Li in the composite metal oxide. When the proportion of metal elements other than Li in the Li layer exceeds 8 mol%, the diffusivity of Li ions in the Li layer decreases, sometimes resulting in a decrease in battery capacity. The metal elements other than Li present in the Li layer are mainly Ni, but other metal elements may also be included. The proportion of metal elements other than Li in the Li layer is, for example, greater than 0.1 mol%.

[0059] The ratio of metal elements other than Li in the layered Li layer can be obtained from the Rietveld analysis results of the X-ray diffraction pattern of the composite metal oxide obtained by the above X-ray diffraction measurement. The Rietveld analysis of the X-ray diffraction pattern can be performed using, for example, Rietveld analysis software, PDXL2 (Rigaku Corporation).

[0060] In the composite metal oxide, the ratio m / n of the half-value width m of the diffraction peak of the (003) plane of the X-ray diffraction pattern based on X-ray diffraction to the half-value width n of the diffraction peak of the (110) plane is 0.75≤m / n. When m / n is less than 0.75, the strain of the layered structure is too large, causing the layered structure to become brittle. The upper limit of m / n is, for example, 0.85. When m / n exceeds 0.85, the battery capacity sometimes decreases.

[0061] The X-ray diffraction pattern was obtained by a powder X-ray diffraction method under the following conditions using a powder X-ray diffractometer (trade name "RINT-TTR" manufactured by Rigaku Corporation, radiation source Cu—Kα).

[0062] Measuring range: 15-120°

[0063] Scanning speed: 4° / min

[0064] Analysis range: 30-120°

[0065] Background: B-Splines

[0066] Profile function: segmented pseudo-Voigt function

[0067] Constraint: Li(3a)+Ni(3a)=1

[0068] Ni(3a)+Ni(3b)=α (α is the content ratio of each Ni)

[0069] ICSD No.:98-009-4814

[0070] From the perspective of increasing the capacity of the battery and improving the output characteristics of the battery, the crystallite size s of the composite metal oxide calculated by the Scherrer equation from the half-value width of the diffraction peak of the (104) plane of the X-ray diffraction pattern based on X-ray diffraction is preferably The Scherrer formula is shown below. In the formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-value width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.

[0071] s=Kλ / Bcosθ

[0072] In addition to the positive electrode active material of the present embodiment, the positive electrode mixture layer may also contain other positive electrode active materials, such as composite metal oxides having primary particles with an aspect ratio of 2 or more and less than 35%, and composite metal oxides without a surface modification layer.

[0073] Next, an example of a method for producing a positive electrode active material according to the present embodiment is described. The method for producing a positive electrode active material includes, for example, a step of mixing a metal oxide containing at least Ni, a Li raw material, and at least one of a Ca raw material and a Sr raw material to obtain a mixture, and a step of calcining the mixture to obtain a positive electrode active material.

[0074] Metal oxides can be made by dropping a solution of metal salts such as Ni, Co, Mn, etc., and an alkaline solution such as sodium hydroxide in a reaction tank in which a pH-adjusted solution is stirred, and adjusting the pH to the alkaline side (e.g., 8.5 to 12.5) so that a composite hydroxide is precipitated (coprecipitated) and the composite hydroxide is heat-treated. The aspect ratio of the composite metal oxide can be adjusted by changing the conditions for precipitating the composite hydroxide (concentration of the solution added, pH in the reaction tank, solution temperature in the reaction tank, complexing agent, etc.) and the conditions for heat treatment (heat treatment temperature, heat treatment time, heat treatment atmosphere, etc.). The heat treatment temperature is preferably below 600°C. For example, in order to increase the aspect ratio of the composite metal oxide, the concentration of the metal salt solution and the alkaline solution added is reduced and heat treatment is performed within a specific temperature range.

[0075] Next, a mixture can be obtained by mixing a metal oxide containing at least Ni, a Li raw material, and at least one of a Ca raw material and a Sr raw material. Examples of the Li raw material include Li 2 CO 3 、LiOH、Li 2 O 2 , Li 2 O、LiNO 3 、LiNO 2 , Li 2 SO 4 、LiOH·H 2 O, LiH, LiF, etc. As the Ca raw material, Ca(OH) 2 、CaHPO 4 , Ca(H 2 PO 4 ) 2 , Ca 3 (PO 4 ) 2 , CaO, CaCO 3 、CaSO 4 、Ca(NO3 ) 2 , CaCl 2 、CaAlO 4 As the Sr raw material, Sr(OH) 2 、SrHPO 4 、Sr(H 2 PO 4 ) 2 , Sr 3 (PO 4 ) 2 、SrO、SrCO 3 、SrSO 4 、Sr(NO 3 ) 2 、SrCl 2 、SrAlO 4 In addition, Me raw materials may be mixed during the mixing. Examples of Me raw materials include ZrO 2 , Nb 2 O 5 , Nb 2 O 5 ·nH 2 O、TiO 2 、Ti(OH) 4 、SiO、SiO 2 , Li 2 MoO 4 、MoO 3 , H 2 MoO 4 , WO 3 , Li 2 WO 4 、Al(OH) 2 、Al 2 O 3 、Al 2 (SO 4 ) 3 、Al(NO 3 ) 3 Mg(OH) 2 、MgO、P 2 O 5 、Fe(OH) 2 , Fe 2 O 3 SnO 2 、Bi(OH) 3 、Bi 2 O 3 , H 3 BO 3 , B 2 O 3 wait.

[0076] The mixture is calcined to obtain a composite metal oxide as a positive electrode active material. The mixture is calcined in an oxygen flow with an oxygen concentration of 60% or more, and the flow rate of the oxygen flow is 10 cm / s. 3 The range of 0.1L / min to 4L / min in the roasting furnace or 1L / min or more per 1kg of the mixture. The first set temperature in the roasting conditions is set to 450°C or less, the holding time of the first set temperature is in the range of 0 hours or more and 8 hours or less, and the heating rate at 450°C or less is greater than 1.5°C / minute and less than 6.0°C / minute. The second set temperature is set to 450°C or more and 680°C or less, the holding time of the second set temperature is in the range of 0 hours or more and 8 hours or less, and the heating rate at 450°C or more and 680°C or less is greater than 1.0°C / minute and less than 4.5°C / minute. In addition, the maximum temperature is in the range of 690°C or more and 900°C or less. The heating rate from greater than 680°C to the maximum temperature can be, for example, 0.1°C / minute to 3.5°C / minute. In addition, the holding time to the maximum temperature can be 1 hour or more and 10 hours or less. In addition, the calcination process can be a multi-stage calcination, and multiple stages can be set in each temperature region as long as it is within the above-mentioned specified range. For example, by changing the first set temperature, the second set temperature, each heating rate until the highest temperature is reached, and each holding time, the crystallinity of the composite metal oxide is changed, thereby adjusting the value of the half-value width ratio m / n.

[0077] The prepared composite metal oxide may subsequently undergo a water washing and drying process and a heat treatment process. The water washing and drying process may be carried out using known methods and conditions. It should be noted that the Me raw material may be added to the filter cake-like composition after water washing or during the heat treatment process. The heat treatment process may be carried out, for example, in a vacuum, in an oxygen flow, or in the atmosphere at a temperature of 150°C to 600°C. Examples of the Me raw material added after water washing or during the heat treatment process include tungsten oxide (WO 3 ), lithium tungstate (Li 2 WO 4 , Li 4 WO 5 , Li 6 W 2 O 9 ), boric acid (H 3 BO 3 ), lithium borate (Li 2 B 4 O 7 , Li 3 BO 3 , LiB 3 O 5 、LiBO 2), aluminum oxide (Al 2 O 3 ), aluminum sulfate (Al 2 (SO 4 ) 3 )wait.

[0078] [negative electrode]

[0079] The negative electrode 12, for example, has a negative electrode collector and a negative electrode mixture layer formed on the surface of the negative electrode collector. The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. The negative electrode collector can use a foil of a metal such as copper or copper alloy that is stable within the potential range of the negative electrode 12, a thin film having the metal configured on the surface, and the like. The thickness of the negative electrode collector is, for example, 5 μm to 30 μm. The negative electrode mixture layer contains, for example, a negative electrode active material and a binder. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm on one side of the negative electrode collector. The negative electrode 12 can be produced, for example, by coating a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. on the surface of the negative electrode collector, drying the coating, and then rolling the negative electrode mixture layer to form the negative electrode mixture layer on both sides of the negative electrode collector.

[0080] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and carbon materials such as graphite are generally used. The graphite can be any natural graphite such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads. In addition, as the negative electrode active material, metals such as Si and Sn alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can be used. In addition, materials having a carbon coating thereon can also be used. For example, SiO x (0.5≤x≤1.6) or a Si-containing compound represented by Li 2y SiO (2+y) A Si-containing compound in which Si fine particles are dispersed in a lithium silicate phase represented by (0<y<2) or the like can be used in combination with graphite.

[0081] As the binder contained in the negative electrode mixture layer, for example, styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (which may be PAA-Na, PAA-K, etc., or partially neutralized salt), polyvinyl alcohol (PVA), etc. can be listed. They can be used alone or in combination of two or more.

[0082] [Separator]

[0083] For example, the separator 13 can use a porous sheet with ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. As the material of the separator, polyolefins such as polyethylene and polypropylene, cellulose, etc. are preferred. The separator 13 can be a single-layer structure or a laminated structure. In addition, a resin layer with high heat resistance such as an aromatic polyamide resin or a filler layer containing a filler of an inorganic compound can be provided on the surface of the separator 13.

[0084] [Non-aqueous electrolyte]

[0085] The non-aqueous electrolyte, for example, comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent can use, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of more than two of them. The non-aqueous solvent can contain a halogen substituted substance formed by replacing at least a portion of hydrogen in these solvents with a halogen atom such as fluorine. As the halogen substituted substance, fluorinated cyclic carbonates such as fluorinated ethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as methyl fluoropropionate (FMP), etc. can be listed.

[0086] Examples of the above-mentioned esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP); and the like.

[0087] Examples of the ethers include cyclic ethers such as 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, and crown ethers; 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, and ethylethylene. 1,2-Dimethoxyethane, 1,2-Dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-Diethoxyethane, 1,2-Diethoxyethane, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.

[0088] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF 4 、LiClO 4、LiPF 6 、LiAsF 6 、LiSbF 6 、LiAlCl 4 、LiSCN、LiCF 3 SO 3 、LiCF 3 CO 2 、Li(P(C 2 O 4 )F 4 )、LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, Li 2 B 4 O 7 、Li(B(C 2 O 4 )F 2 ) and other borates, LiN(SO 2 CF 3 ) 2 、LiN(C 1 F 2l+1 SO 2 )(C m F 2m+1 SO 2 ){l, m is an integer greater than 0} and other imide salts. Lithium salts can be used alone or in combination. Among them, LiPF 6 The concentration of the lithium salt is, for example, 0.5 mol to 2 mol per 1 L of the non-aqueous solvent. In addition, vinylene carbonate or propane sultone-based additives may be added.

[0089] Example

[0090] Hereinafter, the present disclosure will be further described by way of examples and comparative examples, but the present disclosure is not limited to the following examples.

[0091] <Example 1-1>

[0092] [Preparation of positive electrode active material]

[0093] The [Ni 0.80 Co 0.12 Mn 0.08 ](OH) 2The composite hydroxide represented by was calcined at 600°C for 8 hours to obtain a metal oxide (Ni 0.80 Co 0.12 Mn 0.08 O 2 ). Next, ZrO is added to the above metal oxide. 2 and Ca(OH) 2 The molar ratio of Zr to the total amount of metal elements was 0.3 mol %, the molar ratio of Ca to the total amount of metal elements was 0.2 mol %, and lithium hydroxide monohydrate (LiOH·H 2 O) so that the molar ratio of Li to the total amount of Ni, Co, Mn, Zr and Ca is 103 mol % to obtain a mixture. The mixture is heated from room temperature to 400°C at a heating rate of 4°C / min under an oxygen flow with an oxygen concentration of 95% (a flow rate of 3L / min per 1kg of the mixture), and then, from 400°C to 650°C at a heating rate of 2°C / min. Then, the temperature is raised from 650°C to 850°C at a heating rate of 1°C / min and maintained for 6 hours to obtain a composite metal oxide. The composite metal oxide is washed with water and dried to obtain the positive electrode active material of Example 1-1.

[0094] The obtained positive electrode active material was measured using an ICP emission spectrometer (iCAP6300 manufactured by Thermo Fisher Scientific), and the elements shown in Table 1 described later were confirmed as elements other than Li and O. In addition, by TEM-EDX, it was confirmed that a surface modification layer containing Ca existed on the surface of the primary particles including the surface of the secondary particles of the positive electrode active material.

[0095] [Production of positive electrode]

[0096] 95 parts by mass of the above-mentioned positive electrode active material, 3 parts by mass of acetylene black (AB), and 2 parts by mass of polyvinylidene fluoride (PVDF) are mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of a positive electrode collector consisting of aluminum foil and the coating is dried, and then the coating is rolled using a calendering roller, cut into a specified electrode size, and a positive electrode is made. It should be noted that an exposed portion exposed on the surface of the positive electrode collector is provided on a portion of the positive electrode.

[0097] [Preparation of non-aqueous electrolyte]

[0098] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF 6 ) is dissolved in the mixed solvent to prepare a non-aqueous electrolyte.

[0099] [Preparation of test battery]

[0100] The positive electrode lead was attached to the exposed part of the positive electrode, and the negative electrode lead was attached to the Li metal foil as the negative electrode, and the positive electrode and the negative electrode were wound into a spiral shape with a polyolefin separator interposed therebetween, and then radially pressed to form a flat wound electrode body. The electrode body was housed in an outer casing composed of an aluminum laminate sheet, the above-mentioned nonaqueous electrolyte was injected, and then the opening of the outer casing was sealed to obtain a test battery.

[0101] [Evaluation of charge and discharge efficiency]

[0102] Under a temperature environment of 25°C, constant current charging was performed at a constant current of 0.2C until the battery voltage reached 4.3V, and constant voltage charging was performed at 4.3V until the current value reached 0.01C, and the charge capacity C1 was measured. Then, constant current discharge was performed at a constant current of 0.5C until the battery voltage reached 2.5V, and the discharge capacity C2 at 0.5C was measured. The charge and discharge efficiency at 0.5C was calculated by the following formula.

[0103] Charge and discharge efficiency (%) = C2 / C1×100

[0104] <Example 1-2>

[0105] In the process of preparing the positive electrode active material, the composite hydroxide was calcined at 300°C for 8 hours to obtain a metal oxide, to which TiO 2 To replace ZrO 2 , except for this, a test cell was prepared and evaluated in the same manner as in Example 1-1.

[0106] <Example 1-3>

[0107] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the following points were changed in the preparation process of the positive electrode active material: TEM-EDX confirmed that a surface modification layer containing Ca and Sr existed on the surface of the primary particles including the surface of the secondary particles of the positive electrode active material.

[0108] (1) The composite hydroxide was calcined at 300°C for 4 hours to obtain a metal oxide.

[0109] (2) Adding Nb to the metal oxide 2 O 5 , Ca(OH) 2 and Sr(OH) 2 The molar ratio of Nb, the molar ratio of Ca, and the molar ratio of Sr were 0.5 mol %, 0.3 mol %, and 0.2 mol % with respect to the total amount of metal elements.

[0110] (3) Mixed lithium hydroxide monohydrate (LiOH·H 2 O) such that the molar ratio of Li relative to the total amount of Ni, Co, Mn, Nb, Sr and Ca is 105 mol%.

[0111] <Example 1-4>

[0112] A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the following points were changed in the preparation process of the positive electrode active material.

[0113] (1) The [Ni 0.82 Co 0.12 Mn 0.06 ](OH) 2 The composite hydroxide represented by was calcined at 400°C for 10 hours to obtain a metal oxide (Ni 0.82 Co 0.12 Mn 0.06 O 2 ).

[0114] (2) Adding SiO to the metal oxide 2 、Al(OH) 3 and Ca(OH) 2 The molar ratios of Si, Al and Ca were each 0.5 mol % with respect to the total amount of the metal elements.

[0115] (3) The mixture was heated from room temperature to 500°C at a heating rate of 2°C / min, then from 500°C to 680°C at a heating rate of 2°C / min, and then from 680°C to 820°C at a heating rate of 2°C / min and maintained for 4 hours to obtain a composite metal oxide.

[0116] <Comparative Example 1-1>

[0117] In the process of preparing the positive electrode active material, the composite hydroxide was calcined at 700°C for 8 hours to obtain a metal oxide, and ZrO 2 A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the amount of Ca was changed to 0.5 mol % and Ca was not added.

[0118] <Comparative Example 1-2>

[0119] In the process of making positive electrode active materials, ZrO is added to metal oxides. 2 The amount of was changed to 0.5 mol %, and no Ca was added, and lithium hydroxide monohydrate (LiOH·H 2A test cell was prepared and evaluated in the same manner as in Example 1-1 except that the molar ratio of Li to the total amount of Ni, Co, Mn and Zr was 101 mol %.

[0120] <Example 2-1>

[0121] In the process of preparing the positive electrode active material, the [Ni 0.92 Co 0.02 Mn 0.06 ](OH) 2 The composite hydroxide represented by was calcined at 400°C for 4 hours to obtain a metal oxide (Ni 0.80 Co 0.12 Mn 0.08 O 2 ). Next, add Mg(OH) 2 , Fe 2 O 3 , Li 2 MoO 4 and Ca(OH) 2 The molar ratio of Mg, Fe, Mo and Ca to the total amount of metal elements was 0.5 mol%, and lithium hydroxide monohydrate (LiOH·H 2 O) The molar ratio of Li to the total amount of Ni, Co, Mn, Mg, Fe, Mo and Ca is 105 mol % to obtain a mixture. The mixture is heated from room temperature to 400°C at a heating rate of 4°C / min under an oxygen flow with an oxygen concentration of 95% (a flow rate of 3 L / min per 1 kg of the mixture), and then maintained at 400°C for 2 hours. Then, the temperature is increased from 400°C to 650°C at a heating rate of 3°C / min. Then, the temperature is increased from 650°C to 730°C at a heating rate of 0.8°C / min and maintained for 4 hours to obtain a composite metal oxide. The composite metal oxide is washed with water and dried to obtain the positive electrode active material of Example 1-2. Then, a test battery is made in the same manner as Example 1-1 and evaluated.

[0122] <Example 2-2>

[0123] In the process of preparing the positive electrode active material, the composite hydroxide was calcined at 100°C for 6 hours to obtain a metal oxide, to which ZrO was added. 2 and Ca(OH) 2 A test cell was prepared and evaluated in the same manner as in Example 2-1 except that the molar ratios of Zr and Ca to the total amount of the metal elements were each 0.5 mol %.

[0124] <Example 2-3>

[0125] A test cell was prepared and evaluated in the same manner as in Example 2-1 except that the following points were changed during the preparation of the positive electrode active material: TEM-EDX confirmed that a surface modification layer containing Ca and Sr existed on the surface of the primary particles including the surface of the secondary particles of the positive electrode active material.

[0126] (1) Metal oxide (Ni) was obtained by coprecipitation 0.92 Mn 0.08 O 2 ), adding Nb to the metal oxide 2 O 5 , WO 3 , Ca(OH) 2 and Sr(OH) 2 The molar ratios of Nb, W and Ca were 0.5 mol % and the molar ratio of Sr was 0.1 mol % with respect to the total amount of metal elements, respectively, to obtain a composite metal oxide.

[0127] (2) After washing and drying the composite metal oxide, H 3 BO 4 Heat treatment was performed at 400° C. in an oxygen flow so that the molar ratio of B to the total amount of Ni and Mn was 1 mol %.

[0128] <Example 2-4>

[0129] In the process of preparing the positive electrode active material, the [Ni 0.93 Mn 0.04 Al 0.03 ](OH) 2 The composite hydroxide represented by was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.93 Mn 0.04 Al 0.03 O 2 ), Sr(OH) is added to the metal oxide 2 A test cell was prepared and evaluated in the same manner as in Example 2-1 except that the molar ratio of Sr to the total amount of metal elements was 1 mol%. By TEM-EDX, it was confirmed that a surface modification layer containing Sr existed on the surface of the primary particles including the surface of the secondary particles of the positive electrode active material.

[0130] <Comparative Example 2-1>

[0131] A test cell was prepared and evaluated in the same manner as in Example 2-1 except that the following points were changed in the preparation process of the positive electrode active material.

[0132] (1) The composite hydroxide was calcined at 700°C for 8 hours to obtain a metal oxide.

[0133] (2) No Mg(OH) is added to the metal oxide 2 , Fe 2 O 3 , Li 2 MoO 4 and Ca(OH) 2 .

[0134] (3) The mixture was heated from room temperature to 400°C at a heating rate of 5°C / min, and then from 400°C to 650°C at a heating rate of 5°C / min. Then, the mixture was heated from 650°C to 730°C at a heating rate of 5°C / min and maintained for 1 hour to obtain a composite metal oxide.

[0135] <Comparative Example 2-2>

[0136] In the process of preparing the positive electrode active material, the [Ni 0.92 Mn 0.08 ](OH) 2 The composite hydroxide represented by is calcined at 800°C for 8 hours to obtain a metal oxide (Ni 0.92 Mn 0.08 O 2 ), adding Ca(OH) 2 and Sr(OH) 2 A test cell was prepared and evaluated in the same manner as in Example 2-1 except that the molar ratios of Ca and Sr to the total amount of the metal elements were each 1 mol %.

[0137] The charge and discharge efficiency of the test cells of the examples and comparative examples are shown in Tables 1 and 2. In addition, Tables 1 and 2 also show the composition of the positive electrode active material, the proportion of primary particles with a high aspect ratio, the presence of Ca and Sr on the surface of the primary particles, the proportion of primary particles with edge faces oriented along the major axis direction, the half-value width ratio m / n, the proportion of metal elements other than Li in the Li layer, and the crystallite size s. The charge and discharge efficiency of the test cells of Examples 1-1 to 1-4 and Comparative Example 1-2 shown in Table 1 is expressed relatively, with the charge and discharge efficiency of the test cell of Comparative Example 1-1 being set to 100. The charge and discharge efficiency of the test cells of Examples 2-1 to 2-4 and Comparative Example 2-2 shown in Table 2 is expressed relatively, with the charge and discharge efficiency of the test cell of Comparative Example 2-1 being set to 100.

[0138] [Table 1]

[0139]

[0140] [Table 2]

[0141]

[0142] In Tables 1 and 2, the charge and discharge efficiency of the test battery of the embodiment is improved compared to the test battery of the comparative example. Therefore, it can be seen that the surface of the positive electrode active material is protected by the surface modification layer containing Ca or Sr, and the positive electrode active material composed of secondary particles contains primary particles with an aspect ratio of 2 or more at a predetermined ratio, thereby specifically improving the charge and discharge efficiency.

[0143] The present disclosure is further described through the following embodiments.

[0144] Scenario 1:

[0145] A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a composite metal oxide,

[0146] The composite metal oxide contains at least one element selected from the group consisting of Li, Na, B, Ni, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi and at least one of Ca and Sr, and includes secondary particles formed by aggregation of primary particles.

[0147] In the secondary particles, the proportion of the primary particles having an aspect ratio of 2 or more is 35% or more relative to the total number of the primary particles,

[0148] A surface modification layer containing at least one of Ca and Sr exists on the surface of the primary particles including the surface of the secondary particles.

[0149] Scenario 2:

[0150] The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the composite metal oxide contains an alkali metal.

[0151] Solution 3:

[0152] The positive electrode active material for a non-aqueous electrolyte secondary battery according to Scheme 2, wherein the sum of the contents of Ca and Sr in the composite metal oxide relative to the total number of moles of metal elements other than the alkali metal is 0 mol%<Ca content+Sr content<2 mol%.

[0153] Solution 4:

[0154] A positive electrode active material for a non-aqueous electrolyte secondary battery according to Scheme 2 or 3, wherein, in the composite metal oxide, the content of Ca relative to the total molar number of metal elements other than the alkali metal and the content of Sr relative to the total molar number of metal elements other than the alkali metal satisfy Ca content > Sr content.

[0155] Solution 5:

[0156] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of aspects 2 to 4, wherein the composite metal oxide contains Mn,

[0157] In the composite metal oxide, the content of Co with respect to the total number of moles of metal elements other than the alkali metal and the content of Mn with respect to the total number of moles of metal elements other than the alkali metal satisfy 0≤Co content / Mn content≤2.

[0158] Solution 6:

[0159] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of schemes 2 to 5, wherein the content of Ni in the composite metal oxide is 50 mol % ≤ Ni content ≤ 95 mol % relative to the total molar number of metal elements other than the alkali metal,

[0160] The content of Co in the composite metal oxide is 0 mol % ≤ Co content ≤ 15 mol % relative to the total molar number of metal elements excluding the alkali metal.

[0161] Solution 7:

[0162] The positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of aspects 2 to 6, wherein the composite metal oxide has a layered structure in which alkali metal layers and Me layers are alternately stacked.

[0163] Solution 8:

[0164] The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 7, wherein, in the secondary particles, the ratio of the primary particles in which the edge faces of the alkali metal layer and the edge faces of the Me layer are oriented in the major axis direction is 70% or more relative to the total number of the primary particles.

[0165] Solution 9:

[0166] The positive electrode active material for a non-aqueous electrolyte secondary battery according to aspect 7 or 8, wherein the alkali metal is Li, and the alkali metal layer is a Li layer.

[0167] Solution 10:

[0168] The positive electrode active material for a non-aqueous electrolyte secondary battery according to embodiment 9, wherein the ratio of the metal element other than Li present in the Li layer is 8 mol % or less relative to the total number of moles of the metal element other than Li in the composite metal oxide.

[0169] Solution 11:

[0170] The positive electrode active material for a non-aqueous electrolyte secondary battery according to Scheme 9 or 10, wherein the crystallite size s of the composite metal oxide calculated by the Scherrer equation from the half-value width of the diffraction peak of the (104) plane of the X-ray diffraction pattern based on X-ray diffraction is

[0171] Solution 12:

[0172] A positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of Schemes 9 to 11, wherein in the composite metal oxide, the ratio m / n of the half-width m of the diffraction peak of the (003) plane in the X-ray diffraction pattern based on X-ray diffraction to the half-width n of the diffraction peak of the (110) plane is 0.75≤m / n.

[0173] Solution 13:

[0174] A nonaqueous electrolyte secondary battery comprising: a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery according to any one of aspects 1 to 12; a negative electrode; and a nonaqueous electrolyte.

[0175] Description of Reference Numerals

[0176] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating component, 26 upper valve body, 27 cover, 28 gasket, 30 high aspect ratio primary particles, 32 edge surface of Li layer, 34 edge surface of Me layer.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a composite metal oxide, The composite metal oxide contains at least one element selected from the group consisting of Li, Na, B, Ni, Mg, Al, Si, P, K, Ti, Mn, Fe, Co, Zr, Nb, Mo, Sn, W and Bi and at least one of Ca and Sr, and includes secondary particles formed by aggregation of primary particles. In the secondary particles, the proportion of the primary particles having an aspect ratio of 2 or more is 35% or more relative to the total number of the primary particles, A surface modification layer containing at least one of Ca and Sr exists on the surface of the primary particles including the surface of the secondary particles.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein The composite metal oxide contains an alkali metal.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein The total content of Ca and Sr in the composite metal oxide is 0 mol%<Ca content+Sr content<2 mol% relative to the total number of moles of metal elements other than the alkali metal.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein In the composite metal oxide, a content rate of Ca with respect to the total number of moles of metal elements other than the alkali metal and a content rate of Sr with respect to the total number of moles of metal elements other than the alkali metal satisfy Ca content>Sr content.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein The composite metal oxide contains Mn, In the composite metal oxide, the content of Co with respect to the total number of moles of metal elements other than the alkali metal and the content of Mn with respect to the total number of moles of metal elements other than the alkali metal satisfy 0≤Co content / Mn content≤2.

6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein The content of Ni in the composite metal oxide is 50 mol%≤Ni content≤95 mol% relative to the total molar number of metal elements other than the alkali metal, The content of Co in the composite metal oxide is 0 mol % ≤ Co content ≤ 15 mol % relative to the total molar number of metal elements excluding the alkali metal.

7. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 2, wherein The composite metal oxide has a layered structure in which alkali metal layers and Me layers are alternately stacked.

8. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 7, wherein In the secondary particles, the ratio of the primary particles in which the edge faces of the alkali metal layer and the edge faces of the Me layer are oriented in the major axis direction is 70% or more relative to the total number of the primary particles.

9. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 7, wherein The alkali metal is Li, and the alkali metal layer is a Li layer.

10. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 9, wherein The ratio of the metal element other than Li present in the Li layer is 8 mol % or less relative to the total number of moles of the metal element other than Li in the composite metal oxide.

11. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 9, wherein The crystallite size s of the composite metal oxide calculated from the half-value width of the diffraction peak of the (104) plane of the X-ray diffraction pattern based on X-ray diffraction by the Scherrer formula is:

12. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 9, wherein In the composite metal oxide, a ratio m / n of a half-value width m of a diffraction peak of a (003) plane to a half-value width n of a diffraction peak of a (110) plane in an X-ray diffraction pattern based on X-ray diffraction is 0.75≤m / n. 13 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , a negative electrode, and a non-aqueous electrolyte.